2022
DOI: 10.1002/ecs2.4266
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in autumn temperature has stabilized tree growth in forests near the tree lines in Chilean Patagonia

Abstract: It is widely accepted that global warming is affecting forests near the tree line by increasing tree growth in these cold-limited environments. However, since about 1970, a reduction in tree growth near the tree line has been observed in response to warming and increased drought stress. This reduction in tree growth has been mainly reported in forests of the northern hemisphere but less studied in southern forests. In this study, we investigated tree populations of Nothofagus pumilio located near the arboreal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Furthermore, understanding how resilient lenga forests are to disturbances of this spatio-temporal scale is relevant, as to date they seem to continue increasing in severity and frequency in the region. This is particularly relevant in the context of climate change, as it has been shown that increasing temperatures and drought conditions are generating changes in tree growth, increasing tree mortality in these forests [9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, understanding how resilient lenga forests are to disturbances of this spatio-temporal scale is relevant, as to date they seem to continue increasing in severity and frequency in the region. This is particularly relevant in the context of climate change, as it has been shown that increasing temperatures and drought conditions are generating changes in tree growth, increasing tree mortality in these forests [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Because the drier and warmer conditions seem to have been the new baseline conditions for southern Patagonia since the 1980s [9], an increase in the frequency and magnitude of the outbreaks is expected. In this short communication, we describe the new 2019 and 2022 record-breaking outbreaks of O. amphimone in terms of size and intensity.…”
Section: Introductionmentioning
confidence: 99%